2013
DOI: 10.3892/ijmm.2013.1279
|View full text |Cite
|
Sign up to set email alerts
|

DEC1 is positively associated with the malignant phenotype of invasive breast cancers and negatively correlated with the expression of claudin-1

Abstract: Abstract. Differentiated embryo-chondrocyte expressed gene 1 (DEC1) is a basic helix-loop-helix transcriptional regulator, reportedly involved in cell growth, differentiation, apoptosis and tumorigenesis. In breast cancer, DEC1 expression correlates with increased malignant potential and invasiveness. Nevertheless, the detailed mechanisms by which DEC1 modulates breast cancer progression are still unclear. Claudin-1, an important tight junction protein, functions as a tumor invasion suppressor. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…However, no significant changes in Bhlhe40 mRNA expression were observed in iNKT cells of mice subjected to dark/light cycles, suggesting that the functions of Bhlhe40 in iNKT cells are independent of the circadian rhythm. Bhlhe40 was shown to control various functions of T cells, such as turning of naïve CD8 + T cells into memory ones, cytokine productions, or tumor infiltration, in a circadian rhythm-independent manner (43)(44)(45). Similarly, in this study, we report a previously unidentified function for Bhlhe40 as an enhancer of IFN-γ production in iNKT cells that is also independent of the circadian rhythm.…”
Section: Bhlhe40 -/-Inktsupporting
confidence: 52%
“…However, no significant changes in Bhlhe40 mRNA expression were observed in iNKT cells of mice subjected to dark/light cycles, suggesting that the functions of Bhlhe40 in iNKT cells are independent of the circadian rhythm. Bhlhe40 was shown to control various functions of T cells, such as turning of naïve CD8 + T cells into memory ones, cytokine productions, or tumor infiltration, in a circadian rhythm-independent manner (43)(44)(45). Similarly, in this study, we report a previously unidentified function for Bhlhe40 as an enhancer of IFN-γ production in iNKT cells that is also independent of the circadian rhythm.…”
Section: Bhlhe40 -/-Inktsupporting
confidence: 52%
“…We have previously reported that BHLHE40 negatively correlated with the expression of CLDN1 in breast cancer . Therefore, we focused on the role of BHLHE40 in regulating CLDN1 transcription.…”
Section: Resultsmentioning
confidence: 99%
“…Our study confirms the possible influence of hypomethylation and upregulated expression of CRY1 in prognostically poor IGHV unmutated CLL and further emphasises its role as potential biomarker for relative risk of treatment initiation and TTFT in early stage CLL. In addition to CRY1 , three other circadian rhythm genes NPAS2 , BHLHE40 , and ARNTL were also observed to be hypomethylated in the unmutated subgroup [52]. …”
Section: Discussionmentioning
confidence: 99%